Methods of Teaching Historical Syntax to Future Linguists (Journal of Educational Sciences, 2025)
The article discusses the scientific and methodological foundations of the system of teaching historical syntax to future linguists on the basis of the work «Gulistan bit Turki». This monument, written by Saif Saray in the XIV century, is a valuable source in the historical development of Turkic literature and language. Historical syntax is an important area that studies the evolution of the grammatical structure of a language, the training of which contributes to a deep understanding of the laws of language development and professional development by future specialists.The purpose of the study is to provide an effective methodology for teaching historical syntax by analyzing the syntactic features of the text «Gulistan bit Turki». The article examines the ways of historical development of phrases and sentence structures in the text and determines their linguistic features. In addition, methods and techniques that can be used in teaching the text are proposed, including interactive learning technologies and approaches aimed at developing students research abilities.As a result of the research work, it was shown that the use of the work «Gulistan bit Turki» as an educational material increases the level of knowledge of historical linguistics of future linguists and allows them to improve their analytical and creative abilities. By studying the syntactic structures of the monument, students get not only grammatical knowledge, but also the opportunity to more deeply understand the historical and cultural heritage of the Turkic languages. This study will contribute to improving the quality of training of future specialists and modernizing the practice of teaching historical linguistics.Key words: Chagatai language, Gulistan bit Turki, historical syntax, teaching methods, Turkic languages.